Mental Toughness and Problem-Solving Skills from a Psychological Perspective: A Study on Physically Disabled Athletes. - Şahİnler, Yunus; Ersoy, Adnan (Palaestra, 2025)
The aim of the study was to examine the mental endurance and problem-solving skill levels of athletes with physical disabilities and whether there were differences between the variables. The study consisted of athletes with physical disabilities living in Istanbul, Antalya, and Ankara in 2021-2022. There were a total of 220 athletes, 66 women and 154 men, with physical disabilities in the national teams and camps. In the study, a personal information form, Mental Toughness in Sports Inventory Scale and Problem-Solving Skills Inventory Scale were applied to participants. Data were analyzed by SPSS 26.0 and AMOS 24.0 software packages. Information about the participants, inventory and scale averages, and frequency (f) and percentage (%) values were determined. Since the scales showed normal distribution, parametric tests were applied. As statistical procedures, Kolmogorov-Smirnov and Shapiro Wilk Test, Independent Sample T-Test, One-Way Anova analysis, Tukey test, Pearson Correlation Coefficient Analysis, Multiple Regression and Confirmatory Factor analysis were applied to determine the direction of significance. The significance level was determined as p<0.05. As a result of the analyses, no significant difference was detected between the mental endurance and problem-solving skill levels of physically disabled athletes and the variables of gender, age, sports year, and being a national athlete. However, a significant difference was detected in the variables of education level and branch. As a result of the correlation analysis, it was seen that there was a positive relationship between mental toughness and problem-solving skills of athletes with physical disabilities and that mental toughness also had an effect on problem-solving skills.